Anxiety -Depression psychopathology of a patient with voyeurism, major depression and premature ejaculation - Nurazah, Ismail; Rohayah, Husain; Hatta, Sidi (2017)
This case report highlights a case of young male referred for psychiatric evaluation due to paraphilic disorder. This 27-year old single male working as an assistant accountant was noted to have voyeuristic behaviour and presented with depressive symptoms since his teenage age. He has poor coping whenever he experiences stress in life. He started to watch pornographic videos and subsequently get involved by peeping pre-pubescent’s undergarments. These activities are followed by a compulsive behaviour such as masturbation to gratify his sexual arousal. Results: The patient undergone several psychotherapy sessions, and medical report was furnished for the court's purpose. Our assessment revealed that he was suffering from a lifetime major depressive disorder, and he was prescribed with Tablet Sertraline 50mg/daily. He also has premature ejaculation, severe in nature. He regretted his voyeuristic urge and psychotherapy focused on how to channel his sexual needs. Conclusion: Mood disorder is seen in paraphilic disorder and has to be dealt with in order to establish good management care. ASEAN Journal of Psychiatry, Vol. 18 (2): July – December 2017: XXXX.